2020
DOI: 10.3390/nano10101943
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Zn-Doped Mesoporous Bioactive Glass Nanoparticles in Etch-and-Rinse Adhesive on the Microtensile Bond Strength

Abstract: The purpose of this study was to assess the effects in the dentin bond strength of dental adhesives (DAs) and biological effects using zinc (Zn)-doped mesoporous bioactive glass nanoparticles (MBN-Zn). Synthesized MBN and MBN-Zn were characterized by scanning electron microscopy (SEM), X-ray diffraction and the Brunauer, Emmett and Teller (BET) method. The matrix metalloproteinases (MMP) inhibition effects of DA-MBN and DA-MBN-Zn were analyzed. The microtensile bond strength (MTBS) test was conducted before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…However, over time, hydrolysis occurs in the hybrid layer, resulting in a decrease in long-term stability of the resin-dentin bond [9,19]. Various factors are involved in the decomposition of the hybrid layer, but two of these are the hydrolysis of the polymer and exposed collagen fibers [9,[19][20][21][22]. It has been reported that collagen fibers exposed in the hybrid layer are hydrolyzed by MMPs, thereby reducing the adhesion of the resin restoration to dentin [15,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…However, over time, hydrolysis occurs in the hybrid layer, resulting in a decrease in long-term stability of the resin-dentin bond [9,19]. Various factors are involved in the decomposition of the hybrid layer, but two of these are the hydrolysis of the polymer and exposed collagen fibers [9,[19][20][21][22]. It has been reported that collagen fibers exposed in the hybrid layer are hydrolyzed by MMPs, thereby reducing the adhesion of the resin restoration to dentin [15,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…This result agrees with that found by previous studies in which both toothpastes have showed similar extent of dentinal tubules occlusion (17) . The higher effect of NHA-containing toothpaste has been attributed to elevation of calcium concentrations, causing the remineralization of early caries lesions in an in-situ study (18) . NHA in dentifrice is reported to function by directly filling up micropores on demineralized tooth surfaces, and when it penetrates dentinal tubules it acts as a template in the remineralization process by continuously attracting large amounts of calcium and phosphate ions from the remineralization solution to the tooth tissue, thus promoting crystal integrity and growth (19) .…”
Section: Discussionmentioning
confidence: 96%
“…Determination of cytotoxicity for bioactive materials needs to have a pre-conditioning process [ 58 ] or find the optimal concentration of extract [ 31 , 59 ]. Therefore, in this study, the MTT assay of hDPSCs was cultured in the five different concentrations of Mg-CSC extracts (100, 50, 25, 12.5, 0%).…”
Section: Discussionmentioning
confidence: 99%
“…Human dental pulp stem cells (hDPSCs) were seeded at a density of 5 × 10 4 cells/well in a 48-well plate with 25% diluted extraction medium of Mg-CSC (Mg = 0 to 5 mol%) powder [ 30 , 31 ]. hDPSCs were cultured in α-Minimum Essential Medium (α-MEM, Gibco, Grand Island, NY, USA) containing 10 mM β-glycerophosphate, 50 µg/mL ascorbic acid, and 0.1 µM dexamethasone to induce differentiation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation